2018
DOI: 10.1007/s00432-018-2695-4
|View full text |Cite
|
Sign up to set email alerts
|

Dose-reduced first cycle of chemotherapy for prevention of life-threatening acute complications in nonseminomatous germ cell tumor patients with ultra high tumor markers and/or poor performance status

Abstract: Dose reduction of the first EP cycle by 40-60% in the subgroup of poor risk patients with ultra high tumor marker levels and/or ECOG performance status 3-4 is associated with significantly lowered acute complication rates but not with overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…The 5-years OS rates was 52%, equal in both groups (HR 0.99, 95% CI 0.44–2.26, p = 0.99). However, OS in the group of patients with ultra-high tumor marker levels ( n = 63), compared with the group of other patients with poor-risk ( n = 202), did not differ significantly (HR 0.89, 95% CI 0.58–1.36, P = 0.59 (25, 26).…”
Section: Treatment Outcomementioning
confidence: 92%
See 3 more Smart Citations
“…The 5-years OS rates was 52%, equal in both groups (HR 0.99, 95% CI 0.44–2.26, p = 0.99). However, OS in the group of patients with ultra-high tumor marker levels ( n = 63), compared with the group of other patients with poor-risk ( n = 202), did not differ significantly (HR 0.89, 95% CI 0.58–1.36, P = 0.59 (25, 26).…”
Section: Treatment Outcomementioning
confidence: 92%
“…Based on this knowledge, a reasonably effective approach can be a reduced respectively, shortened course of induction chemotherapy before the administration of consecutive full-dose chemotherapy as the eventual prevention of ARDS development in these patients. All three retrospective studies with modified induction chemotherapy showed non-inferior treatment results compared to full-dose induction chemotherapy (2426). These studies suggest that reduced induction chemotherapy can be helpful to decrease the incidence of ARDS in this group of patients.…”
Section: Treatment Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Testicular cancer is largely found in young and middle-age men, but around 7% of cases occur in children (11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%